Resistance exercise inter-set cooling strategy: Effect on performance and muscle damage - Galoza, P.; Sampaio-Jorge, F.; Machado, M.; Fonseca, R.; Silva, P. A. V. (International Journal of Sports Physiology and Performance, 2011)
Purpose: To compare the effect of inter-set cooling and no cooling during resistance exercise (RE) on the total repetitions and select muscle damage biomarker responses. Methods: Sixteen healthy men volunteered to participate in this study and were randomly assigned to Cooling (n = 8) or Control (n = 8) groups. They performed a RE protocol consisting of four sets of biceps curl at 80% of 1RM. The cooling group received the application of wet bags of ice during each inter-set rest interval (Cooling), while the Control realized the same protocol without ice application. Exercise was performed to voluntary fatigue and the numbers of repetitions per set were recorded. Subjects provided blood samples before and at 24, 48, and 72 h following RE to evaluate serum CK activity and myoglobin concentration. Results: The Cooling group produced a greater number of repetitions (approx. 21%) than did the Control, but there were no differences in serum CK activity and myoglobin responses between the groups. Conclusion: Incorporating inter-set external cooling augments the number of repetitions per set during RE without inducing an additional muscle damage biomarker response.